2022
DOI: 10.3390/diseases10020026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Per- and Polyfluoroalkyl Substances and Allostatic Load among Adults in Various Occupations

Abstract: Objective: This study sought to assess the associations between occupation, serum concentrations of selected of Per- and Polyfluoroalkyl Substances (PFAS), and chronic physiological stress, as operationalized by Allostatic Load (AL), among adults aged ≥20 years. Methods: To explore the interactions of occupation with PFAS levels and AL, data from the National Health and Nutrition Examination Survey (NHANES) 2007–2014 were used. We performed Poisson regression modeling to evaluate AL’s relationships with PFAS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…Occupation plays a pivotal role in determining stress levels [ 40 , 41 ]. High-stress occupations with demanding work environments can lead to elevated stress, burnout, and negative impacts on mental and physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Human exposure to PFAS can occur in occupational settings [ 6 ] via cutaneous contact and inhalation. Non–occupational sources such as contaminated drinking water, and seafood (especially fish), are additional sources of exposure.…”
Section: Introductionmentioning
confidence: 99%